Analysis of The Criminal Act of Child Neglect By Parents Drug Abuse From The Perspektivctive of Islamic Criminal Law - Putra, Andhika Jaya; Damanik, Lia Agustina (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2023)
The crime of child neglect by drug abusing parents is a serious problem that has significant social and humanitarian impacts. In the perspective of Islamic criminal law, the act of child neglect caused by drug abuse by parents is considered an act that violates sharia law and is detrimental to the welfare of society. Analysis of the crime of child neglect by drug abusing parents from the perspective of Islamic criminal law involves interpreting the principles of Islamic law relating to the protection of children's rights, parental obligations, and sanctions for violations of the law. In Islam, parents have a great responsibility to care for, educate and protect their children, and the act of child neglect caused by drug abuse is a serious violation of this obligation. From the perspective of Islamic criminal law, the criminal act of child neglect by drug abusing parents can be classified as an act that harms society and contradicts the principles of social justice. As a result, the perpetrators of such criminal acts may be subject to criminal sanctions in accordance with the applicable sharia law, which may include fines, corporal punishment, or other penalties appropriate to the severity of the offense. However, in applying punishment to perpetrators of the crime of child neglect by drug abusing parents, the Islamic criminal law system also considers mitigating factors such as the intention, psychological condition, and social environment of the perpetrator. Principles such as mercy, justice, and restoration are also upheld in Islamic law enforcement, which allows room for rehabilitation and reintegration of offenders into society. Thus, the analysis of the crime of child neglect by drug abusing parents from the perspective of Islamic criminal law emphasizes the importance of safeguarding the welfare of children and upholding social justice in society. Law enforcement based on the principles of Islamic law can provide a strong basis for protecting children's rights and ensuring that perpetrators of criminal acts are given sanctions that are balanced and beneficial to the common good.